COLONIALISM TOWARDS CHINESE SOCIETY IN W. SOMERSET MAUGHAM’S THE PAINTED VEIL - Pramesti, Endah (LANTERN (Journal on English Language, Culture and Literature), 2014)
In this paper, the writer is interested to analyze colonialism in William Somerset Maugham’s The Painted Veil. The purposes of the thesis are to analyze how the British colonization works during the cholera epidemic in China, to analyze how the response of China society about British colonization, and to analyze the perspective of the Western toward the Eastern which is implied in The Painted Veil. In doing this research, the writer uses method of library research. The object of the thesis is William Somerset Maugham’s The Painted Veil and the supporting data are any information related to the analysis of the object which are taken from the library or internet. The writer also uses postcolonial approach to help explain the issues in The Painted Veil. To investigate the issues, the writer uses colonialism theory by Ania Loomba. The results of the thesis is that British colonialism in China has three purposes. Those are: gold which is related to the economy domination, gospel or christianization, and glory which is related to domination of a nation. The colonialism results in positive and negative response from the Chinese. There is also the view from the Western toward the Eastern. The negative views from the West are stereotypes on how the West looks at the East. The Western thinks that their culture, appearance, manner, belief, and education are better than the Eastern. There is a line boundary between the West and the East. The line boundary makes a nation is different from the other.